Mind-Mapping Technique as a Learning Tool for Epidemiology of Common Diseases Course among Public Health Students - Cheraghi, Maria; Khafaie, Morteza; Tavakol, Heshmatollah; Rahimi, Zahra; Arastoo, Aliasgar (International Journal of Education and Cognitive Sciences, 2022)
Background: One of the most important advantages of using mind -mapping technique is to activate both hemispheres of brain to remember the content easily. We aimed to assess the Mind Mapping technique as an alternative method in the epidemiology of common diseases course. Methodology: The epidemiology of common diseases lesson was taught using Mind-Mapping technique during fourteen sessions. To assess the efficacy and desirability of this technique compared to other traditional methods, the scores obtained by the students those were taught based on Mind-Mapping technique during two years were compared to ones obtained by those who were taught this lesson based on other techniques. In descriptive statistics, mean and standard deviation and in analytic statistics, independent t-test was used. Data analysis was performed using SPSS software version 23. Results: In the first group (n: 41 people), the mean and standard deviation of the students’ scores in the common epidemiology was 1390±2.59 before applying the Mind-Mapping technique. During two years, Public Health under graduates were taught using the Mind-Mapping technique. In the first year, in the second group (n: 33 people), the mean and standard deviation was 16.91±1.82 and in the third group (n: 39 people), in the second year, it was 16.05±1.58. To compare applying the traditional teaching methods to applying Mind-Mapping technique, a statistical significant difference was shown (respectively P>0.001 and P>0.001). Discussion: This study and other studies have shown positive effects of applying Mind-Mapping technique in teaching epidemiology lesson.